The online job market trace in Latin America and the Caribbean - Hilbert, Martin (United Nations, 2020)
Online platforms for labour markets are the most noticeable current innovation in today's job marketplace, and therefore one of the most tangible solutions to tackle several of the objectives outlined in Sustainable Development Goal 8 ("Decent Work and Economic Growth"). While these platforms play an increasingly important role in the day-to-day of workers and employers, very little is known about their constitution and role, and what they can reveal about labour market dynamics in general.This reports contributes to the following aspects to the ongoing discussion: Tracking new developments, Geographical reach, Supply and demand,Temporal dynamics, Detailed insights, Interactive analysis